Response of Macroeconomic Indicators to External Shocks in Indonesia - Febrian, Putri Hana; Wahed, Mohammad (Journal of Business Management and Economic Development, 2025)
As a developing country with a high level of economic openness, Indonesia is classified as vulnerable to global economic dynamics. This study aims to analyze the response to external shocks, namely the COVID-19 pandemic, the Fed's interest rate increase, and USD/IDR exchange rate fluctuations on Indonesia's macroeconomic indicators, namely Gross Domestic Product (GDP) and Consumer Price Index (CPI), as well as evaluate the government's fiscal policy in responding to these pressures during the 2013–2023 period. The research used secondary data for the quarter 2013:Q1 and 2023:Q4, with as many as 44 observations of each variable, using the Vector Error Correction Model (VECM) method. The results of the estimate show that the USD/IDR exchange rate and the Fed's interest rate have a significant long-term relationship with Indonesia's real GDP and CPI. Throughout the research period, the government responded through various fiscal policies such as fuel subsidy adjustments (2013–2014), strengthening infrastructure and tax reform (2015–2019), large stimulus through the PEN program during the pandemic (2020–2022), and returning to fiscal discipline in 2023 with a focus on social protection, human resource development, and industrial downstreaming. These findings underscore the importance of adaptive fiscal policies in mitigating the impact of external shocks on the domestic economy.